2010
DOI: 10.1091/mbc.e09-05-0412
|View full text |Cite
|
Sign up to set email alerts
|

Initial Polarized Bud Growth by Endocytic Recycling in the Absence of Actin Cable–dependent Vesicle Transport in Yeast

Abstract: Budding yeast mutants in assembly of actin cables, which are thought to be the only actin structures essential for budding, still could form a small bud. Mutations in actin patch endocytic machineries/endocytic recycling factors inhibited this budding, suggesting a mechanism that promotes polarized growth by local recycling of endocytic vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 88 publications
0
33
0
1
Order By: Relevance
“…In addition, Cdc42 is associated with two different populations of secretory vesicles (Orlando et al 2011). In contrast, other studies found that Cdc42 and Bem1 could polarize successfully in several mutants with defects in the same actin transport pathway (Yamamoto et al 2010). More importantly, endogenous Cdc42 polarizes at a single cortical site with nearly normal kinetics in cells treated with latrunculin A (LatA), which disrupts all F-actin structures Moseley and Goode 2006).…”
Section: Fks1mentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Cdc42 is associated with two different populations of secretory vesicles (Orlando et al 2011). In contrast, other studies found that Cdc42 and Bem1 could polarize successfully in several mutants with defects in the same actin transport pathway (Yamamoto et al 2010). More importantly, endogenous Cdc42 polarizes at a single cortical site with nearly normal kinetics in cells treated with latrunculin A (LatA), which disrupts all F-actin structures Moseley and Goode 2006).…”
Section: Fks1mentioning
confidence: 97%
“…A specific cdc42 mutant displays exocytosis defects despite seemingly well-polarized actin cables (Adamo et al 2001). In addition, formin and tropomyosin mutants deficient in actin cable assembly still form small buds (Yamamoto et al 2010). Bud emergence and limited bud growth can even occur in the complete absence of F-actin when cells exit from quiescence (Sahin et al 2008).…”
Section: Key Questions Inmentioning
confidence: 99%
“…Targeted secretion and even bud emergence can occur without septin rings (Hartwell 1971;Haarer and Pringle 1987) or actin cables (Sahin et al 2008;Yamamoto et al 2010). However, subsequent bud growth requires actin cables (Yamamoto et al 2010), and proper shaping of the bud requires neck-localized septins (Gladfelter et al 2005).…”
Section: Polarity Establishment In G1mentioning
confidence: 99%
“…Actin perturbations can impair septin ring assembly (Kadota et al 2004;Kozubowski et al 2005;Iwase et al 2006), perhaps suggesting that some septin-organizing factors are delivered by actin cables. And perturbations of vesicle traffic can affect actin polarity (Gao et al 2003) and the localization of Cdc42p (Wedlich-Soldner et al 2004;Irazoqui et al 2005;Zajac et al 2005;Yamamoto et al 2010), although the basis for these effects remains unclear.…”
Section: Polarity Establishment In G1mentioning
confidence: 99%
“…Endocytosis has been proposed to enhance polarization by initiating the recycling of polarity factors (Valdez-Taubas and Pelham, 2003;Marco et al, 2007;Slaughter et al, 2009;Yamamoto et al, 2010;Orlando et al, 2011). In contrast, recent modeling studies have predicted polarized endocytosis to be detrimental to polarity (Layton et al, 2011).…”
Section: Imagingmentioning
confidence: 99%